2009
DOI: 10.1152/ajpcell.00160.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic agonists regulate JAK2/STAT3 signaling to suppress endothelial cell activation

Abstract: The cholinergic anti-inflammatory pathway is a physiological mechanism that inhibits cytokine production and minimizes tissue injury during inflammation. Previous investigations revealed that cholinergic stimulation (via cholinergic agonists and vagus nerve stimulation) suppresses endothelial cell activation and leukocyte recruitment. The purpose of this study was to investigate the mechanisms by which cholinergic agonists (e.g., nicotine and GTS-21) regulate endothelial cell activation. Specifically, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 69 publications
6
72
2
4
Order By: Relevance
“…Our observation that nicotine-induced phosphorylation of JAK2 and STAT3 are inhibited by a-bungarotoxin, represent the first evidence to date indicating activation of the JAK2/STAT3 axis downstream a7-nAChRs in human coronary endothelial cells. Unlike our findings in HCAECs, recent work showed that nicotine treatment of human umbilical vein and dermal microvascular endothelial cells inhibits JAK2/STAT3 [Chatterjee et al, 2009]. Rather than contradictory, these findings likely reflect heterogeneity of endothelial cells derived from different vascular beds in regards to their responsiveness to cholinergic stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation that nicotine-induced phosphorylation of JAK2 and STAT3 are inhibited by a-bungarotoxin, represent the first evidence to date indicating activation of the JAK2/STAT3 axis downstream a7-nAChRs in human coronary endothelial cells. Unlike our findings in HCAECs, recent work showed that nicotine treatment of human umbilical vein and dermal microvascular endothelial cells inhibits JAK2/STAT3 [Chatterjee et al, 2009]. Rather than contradictory, these findings likely reflect heterogeneity of endothelial cells derived from different vascular beds in regards to their responsiveness to cholinergic stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…The anti-inflammatory activity of ACh involves JAK2/STAT3 signaling [36,37]. Previous studies have demonstrated that nicotine acted on macrophages via the recruitment of JAK2 to the α7 nAChR and activation of JAK2, thereby initiating the anti-inflammatory STAT3 signaling cascade [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although the activation or stabilization of transcription factors STAT3 (signal transducer and activator of transcription 3) and HIF-1α (hypoxia-inducible factor 1-alpha) has been demonstrated to play a crucial role in PH pathology [1,[37][38][39], as far as we know there exists no information concerning the effect of ADMA. Interestingly, STAT3 and HIF-1α were shown to be responsible for regulation of cell survival and proliferation, angiogenesis, as well as for inflammatory processes, associated with production of different types of inflammatory-derived mediators described above [37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%